Removal of Chromium(III) Using Synthetic Polymers, Copolymers and their Sulfonated Derivatives as Adsorbents - Farah Kanwal; Muhammad Imran; Liviu Mitu; Zeeshan Rashid; Huma Razzaq; Qurat-Ul-Ain (E-Journal of Chemistry)
This study is concerned with the development of some synthetic polymers, copolymers and their sulfonated derivatives as adsorbents. The effectiveness of these adsorbents in removing Cr(III) from aqueous solution was evaluated by batch technique. The influence of different experimental parameters on removal process such as solution pH, contact time, adsorbent dose, Cr(III) concentration and temperature were evaluated. Adsorption equilibrium was achieved in 20 to 30 min. at pH > 5. The Langmuir, Freundlich and Temkin adsorption isotherms were used to elucidate the observed sorption phenomena. The maximum Cr(III)37.8 mg/gram of PS(polystyrene) and 37.2 mg/g of SAN (styrene/acrylonitrile copolymer) was removed as evaluated from Langmuir isotherm while the heat of sorption was in the range 0.21–7.65 kJ/mol as evaluated from Temkin isotherm. It can be concluded that PS developed in this study exhibited considerable adsorption potential for application in removal of Cr(III) from aqueous media as compared to its copolymers and other derivatives used in this study.